Evaluation of Pneumatic Vs Holmium: YAG Laser Lithotripsy in the Treatment of Ureteric Stone - Bhatta, Pashupati Nath; Raya, Akash; Yadav, Aditya Prakash; Karki, Rishi Kumar; Das, Randhir Kumar; Shrestha, Princes (Janaki Medical College Journal of Medical Science, 2022)
ABSTRACT Background and objectives: Among many lithotripters for fragmentation of ureteric stones, pneumatic and Holmium: YAG laser lithotripsy has reported favorable outcomes. The aim of this study is to compare the efficacy of pneumatic lithotripsy with laser lithotripsy in ureteral stone. Materials and methods: In this prospective study, 60 patients with diagnosis of ureteral calculus underwent ureteroscopic lithotripsy in Urology Unit, Department Surgery, National Medical College and Teaching Hospital over period of 2020 to 2021. They were divided randomly into two groups, each group with 30 patients. Group PL was treated with Pneumatic lithotripsy and Group LL was treated with Holmium: YAG laser lithotripsy. History and detailed clinical examination was performed as per the working proforma which included. Result of both the procedures was assessed. Chi square test were used for correlation analysis. Data analysis was done using SPSS (Statistical Package for social sciences), version 25. Results: Mean age was 26.5 years and 36.33 years in group PL and LL respectively (P=0.58), there was no significant difference in male to female ratio and mean stone in both groups. Duration of operation was significantly lower in LL group and Hospital was slight lower in LL group as compare to PL group (0.95). Conclusion: Ho:YAG laser and pneumatic lithotripsy are efficient and safe procedures for ureteral stones. Though operative time is higher in pneumatic lithotripsy.